2010
DOI: 10.1074/jbc.m110.149575
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycosaminoglycan Sulfation in the Formation of Immunoglobulin Light Chain Amyloid Oligomers and Fibrils

Abstract: Primary amyloidosis (AL) results from overproduction of unstable monoclonal immunoglobulin light chains (LCs) and the deposition of insoluble fibrils in tissues, leading to fatal organ disease. Glycosaminoglycans (GAGs) are associated with AL fibrils and have been successfully targeted in the treatment of other forms of amyloidosis. We investigated the role of GAGs in LC fibrillogenesis. Ex vivo tissue amyloid fibrils were extracted and examined for structure and associated GAGs. The GAGs were detected along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…LC dimers do not efficiently refold from a chaotrope-denatured state; hence, the refolded state could be susceptible to endoproteolysis, although we did not experimentally test this hypothesis herein. It is established that extracellular matrix components hasten the aggregation of amyloidogenic proteins [50, 51], a variable that merits further exploration, although we have not observed such an effect in our experiments to date (data not shown). It is also possible that amyloid fibrils composed of LC fragments can seed or accelerate the aggregation of full-length LCs, although we have not observed this in vitro with these LCs (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…LC dimers do not efficiently refold from a chaotrope-denatured state; hence, the refolded state could be susceptible to endoproteolysis, although we did not experimentally test this hypothesis herein. It is established that extracellular matrix components hasten the aggregation of amyloidogenic proteins [50, 51], a variable that merits further exploration, although we have not observed such an effect in our experiments to date (data not shown). It is also possible that amyloid fibrils composed of LC fragments can seed or accelerate the aggregation of full-length LCs, although we have not observed this in vitro with these LCs (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…8). Although sulfation, carboxylation, and charge pattern of GAGs have been shown to be important for their effect on amyloid formation, this GAG structure-function correlation is not obvious in our results and warrants further investigation [42, 43]. However, our AFM data show that further studies are necessary to better understand the intrinsic effects of sulfation and carboxylation patterns, and saccharide conformation and content, on the aggregation propensity of SAA and other amyloidogenic proteins.…”
Section: Discussionmentioning
confidence: 66%
“…Because of the critical role played by heparin in the coagulation cascade and the importance of heparin-like binding motifs expressed by signaltransducing cellular glycosaminoglycans, there has been considerable interest in identifying and characterizing heparin-binding peptides (34). In addition, several recent in vitro studies have shown that highly sulfated heparin catalyzes the fibrillogenesis of amyloid precursor proteins, including Ig light chains, β-2-microglobulin, Aβ, and sAA, relative to less-sulfated glycosaminoglycans (35)(36)(37). Based on our hypothesis that HS in amyloid is heparin-like, we synthesized a panel of heparinbinding peptides and assessed their ability to bind amyloid in vivo.…”
Section: Resultsmentioning
confidence: 99%